Preferential Impairment of the Contralesional Posterior Semicircular Canal in Internuclear Ophthalmoplegia - Lee, Seung-Han; Kim, Sang-Hoon; Kim, Sung-Sik; Kang, Kyung Wook; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2017)
Background: The vertical vestibulo-ocular reflex (VOR) may be impaired in internuclear ophthalmoplegia (INO) as the medial-longitudinal fasciculus (MLF) conveys VOR-signals from the vertical semicircular canals. It has been proposed that signals from the contralesional posterior semicircular canal are exclusively transmitted through the MLF, while for the contralesional anterior canal other pathways exist. Objective: Here we aimed to characterize dysfunction in individual canals in INO-patients using the video-head-impulse test and to test the hypothesis of dissociated vertical canal impairment in INO. Methods: video-head-impulse testing and MRI were obtained in twenty-one consecutive patients with unilateral (n=16) or bilateral (n=5) INO and 42 controls. VOR-gains and compensatory catch-up saccades were analyzed and the overall function (normal vs. impaired) of each semicircular canal was rated. Results: In unilateral INO, largest VOR-gain reductions were noted in the contralesional posterior semicircular canal (0.55±0.11 vs. 0.89±0.08, p<0.001), while in bilateral INO both posterior (0.43±0.11 vs. 0.89±0.08, p<0.001) and anterior (0.58±0.19 vs. 0.88±0.09, p<0.001) canals showed marked drops. Small, but significant VOR-gain reductions were also found in the other canals in unilateral and bilateral INO-patients. Impairment of overall canal function was restricted to the contralesional posterior canal in 60% of unilateral INO-patients, while isolated involvement of the posterior canal was rare in bilateral INO-patients (20%). Reviewers correctly identified the INO-pattern in 15/21 (71%) patients and in all controls (sensitivity=84.2% [95%-CI=0.59.5-95.8]; specificity=95.5% [95%-CI=83.3-99.2]). Conclusions: Using a video-head-impulse test based overall rating of canal function, the correct INO-pattern could be identified with high accuracy. The predominant and often selective impairment of the contralesional posterior canal in unilateral INO further supports the role of the MLF in transmitting posterior-canal signals. In patients with acute dizziness and abnormal video-head-impulse test-results, central pathologies such as INO should be considered as well, especially when the posterior canal is involved.